3′ uridylation and the regulation of RNA function in the cytoplasm. (26th July 2010) - Norbury, Chris J.
Abstract : Degradation of cytoplasmic mRNAs is an important aspect of the regulation of gene function in eukaryotes. Much of what is currently known about the underlying pathways of mRNA decay is derived from studies of the budding yeast Saccharomyces cerevisiae, in which mRNA turnover is initiated by deadenylation, followed either by decapping and 5′→3′ degradation or by further 3′→5′ exonucleolysis. Our studies using RNA cRACE (circularization-based rapid amplification of cDNA ends) techniques indicate that mRNA decapping in the fission yeast Schizosaccharomyces pombe often does not require prior deadenylation. Furthermore, the poly(A) polymerase-related, cytoplasmic enzyme Cid1 catalyses uridylation of a variety of functionally diverse poly(A) + mRNAs and hence stimulates decapping as part of a novel mRNA turnover pathway. The pathways initiated by uridylation and deadenylation stimulate decapping in a partially redundant fashion, but urg1 mRNA is stabilized in mutants lacking cid1 . Accumulation of uridylated RNAs in an lsm1 mutant suggests an involvement of the Lsm1–7 complex in recognition of the 3′ uridylation tag and recruitment of the decapping machinery. Recent reports from other groups suggest that in metazoans, which unlike budding yeast contain Cid1 orthologues, 3′ uridylation by such enzymes is used to regulate miRNA (microRNA) and siRNA (small interfering RNA) biogenesis and activity. It has further been suggested that uridylation is an important regulatory modification of non-polyadenylated replication-dependent histone mRNAs. This modification may also form the basis of a widespread mechanism for the initiation of the decay of polyadenylated mRNAs in organisms other than fission yeast.